Legal Protection for Victims of Phishing Schemes for Buying & Selling Vehicles On OLX - Gunawan, Rafy Akmal; Nugroho, Andriyanto Adhi (Law Development Journal, 2025)
This study discusses the legal protection of consumers who are victims of phishing schemes in vehicle buying and selling transactions on the OLX digital platform. In the digital era, phishing is one form of cybercrime that is rampant and threatens consumer rights, both as sellers and buyers. Phishing schemes that occur on OLX are generally carried out by impersonating sellers or buyers in order to steal sensitive information and harm other parties financially. This study aims to examine the impact of phishing schemes on consumer rights and analyze the form of legal responsibility of OLX as a platform organizer if consumers experience losses. The method used in this study is normative juridical, with a relevant legal approach such as the Consumer Protection Law, the ITE Law, and the Personal Data Protection Law. The results of the study show that weak identity verification and the lack of monitoring mechanisms from the platform open up loopholes for cybercrime, and put consumers in a vulnerable position. Therefore, there needs to be regulatory updates and strengthening of the legal responsibility of digital platforms to ensure consumer protection in electronic transactions.